2003
DOI: 10.1128/cdli.10.4.520-524.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Major Antigenic Protein 2 of Ehrlichia canis and Ehrlichia chaffeensis and Its Application for Serodiagnosis of Ehrlichiosis

Abstract: Canine monocytic ehrlichiosis, caused by Ehrlichia canis or Ehrlichia chaffeensis, can result in clinical disease in naturally infected animals. Coinfections with these agents may be common in certain areas of endemicity. Currently, a species-specific method for serological diagnosis of monocytic ehrlichiosis is not available. Previously, we developed two indirect enzyme-linked immunosorbent assays (ELISAs) using the major antigenic protein 2 (MAP2) of E. chaffeensis and E. canis. In this study, we further cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Unlike gp19, MAP2 appears to have a mass consistent with that predicted by its amino acid sequence and does not have any serine-rich domains. There is substantial homology among MAP2 orthologs in Ehrlichia spp., and cross-reactions among heterologous MAP2 proteins have been reported (14,17). In contrast, antibodies generated to E. canis gp19 were not crossreactive with E. chaffeensis VLPT, and therefore, these proteins are species-specific orthologs.…”
Section: Vol 75 2007mentioning
confidence: 88%
See 1 more Smart Citation
“…Unlike gp19, MAP2 appears to have a mass consistent with that predicted by its amino acid sequence and does not have any serine-rich domains. There is substantial homology among MAP2 orthologs in Ehrlichia spp., and cross-reactions among heterologous MAP2 proteins have been reported (14,17). In contrast, antibodies generated to E. canis gp19 were not crossreactive with E. chaffeensis VLPT, and therefore, these proteins are species-specific orthologs.…”
Section: Vol 75 2007mentioning
confidence: 88%
“…In contrast, antibodies generated to E. canis gp19 were not crossreactive with E. chaffeensis VLPT, and therefore, these proteins are species-specific orthologs. Other notable differences between MAP2 and gp19 include a major serine-rich linear epitope of gp19 that is strongly recognized by antibodies by Western immunoblotting, while antibodies to MAP2 of E. canis and E. chaffeensis appear to be directed primarily at a conformational epitope (1,2,14). In a previous study, we suggested that the 19-kDa major immunoreactive protein that we identified may be MAP2 (19); however, the data presented in this study support our conclusion that this protein is not MAP2 but rather gp19.…”
Section: Vol 75 2007mentioning
confidence: 99%
“…Fewer of these orthologs have been molecularly identified and characterized in E. ruminantium (MAP1 family [16 genes], MAP2 and mucin-like protein [clone hw26; TRP36/47 ortholog]) [92-94], but additional immunoreactive proteins have been identified in E. ruminantium that have not been described in E. chaffeensis or E. canis [59]. Immunoreactivity of the E. chaffeensis and E. canis MAP2 is primarily dependent on a major conformational epitope that does not react by western immunoblot [95,96], while E. ruminantium MAP2 appears to have a linear B-cell epitope [92]. …”
Section: Immunoprotective Proteinsmentioning
confidence: 99%
“…The msp5 gene of Anaplasma spp. and its ortholog, map2 of Ehrlichia spp., are both known to be highly conserved within the genera Anaplasma and Ehrlichia (2,5,18,20,38). Additionally, based on the amino acid identity of 40.2% among all known orthologs of Msp5/Map2 of Anaplasma and Ehrlichia (3), cross-reactivity among organisms within the genera appears likely when Msp5 of Anaplasma phagocytophilum is used as a test antigen in serologic assays.…”
Section: Discussionmentioning
confidence: 99%